A Prospective Study on Level of Concordance Between Core Needle Biopsy and Surgical Specimen for Assessing Oestrogen Receptor, Progesterone Receptor, and Her2/Neu Receptor Status in Carcinoma Breast and Its Implications on Treatment Decisions - Damodaran, Dileep (Indian J Surg Oncol, 2020)
A prospective study on the level of concordance between core needle biopsy specimen (CNB) and surgical specimen (SS) assesses the oestrogen receptor (ER), progesterone receptor (PR) and Her2/Neu receptor status in Carcinoma breast and its implications on treatment decisions. Ninety consecutive treatment naive operable breast cancer patients treated between September 2015 and April 2017 were included in our prospective study. All patients underwent core needle biopsy prior to definitive surgery. Immunohistochemistry (IHC) studies for ER, PR, and Her2/Neu receptor assay were done in both the CNB specimen and SS. The concordances between CNB specimen and SS for ER, PR, and Her2/Neu receptor were 92%, 88%, and 78% respectively. In our study, overall discordance for ER, PR, and Her2/Neu status based on IHC tests on CNB specimen and its corresponding SS was 41% (37 out of total 90 patients), which was mostly for Her2/Neu (20 patients). Altogether, there was a change in treatment decision based on IHC test results of CNB specimen for 14 out of 37 discordant tests, translating to 15% of the overall study group. Four patients received adjuvant hormonal therapy, and 10 patients got adjuvant Traztuzumab added to their protocol. There is almost perfect to substantial concordance between CNB specimen and SS of IHC tests for ER and PR status. However, the concordance for Her2/Neu receptor is only moderate. Her2/Neu receptor assay by IHC is more sensitive in CNB specimen than in SS.